THE INFLUENCE OF DESPOTIC LEADERSHIP ON EMPLOYEE DISENGAGEMENT IN A DYNAMIC GLOBAL ECONOMY - Wokocha, Tamunoibi Precious (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
This paper reviewed literature on the relationship between despotic leadership and employee quiet quitting. The objectives of the paper were structured in line with assessing the relationship between despotic leadership dimensions such as authoritative behaviour and self-centeredness and outcomes of employee quiet quitting such as employee lacklustre performance and employee low engagement, The paper identified despotic leadership as tyrannical and as necessitating distrust and tension within the workplace, such that it impact negatively on the employee’s behaviour. The paper also adopted the cognitive dissonance theory as it theoretical framework, utilizing the theory as a base for its argument on the implications of the breach between workers expectations and their realities in the work. The paper discovered that these attitudes affect the performance level of the organization in the global market which affects the economy. From the extant literature reviewed on the variables, It was concluded that despotic leadership creates conditions that weaken the morale of employees, lowers their engagement and further leads to their lacklustre performance in the organization. The paper therefore Recommends that organizations should engage leadership responsibilities to transformational and democratic person who will foster employee quite thriving instant of quitting to encourage rapidly changing economy globally, encourage participative leadership and the sharing of power in the workplace for healthier and more collaborative outcomes between leaders and their subordinates.